Suppose that x is a real number such that 4 tan − 1 x + 6 tan − 1 3 x = π . If x 2 = d a − b c , where a , b , c , d are positive integers with g cd ( a , d ) = g cd ( b , d ) = 1 and c is not divisible by the square of any prime, find a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
No Offence to problem setter but i feel it is Highly overrated question
Damn ! I added 23+8+7+81 to 117
can u explain in more detailed manner
L e t tan − 1 x = θ & tan − 1 3 x = α , G i v e n 2 θ + 3 α = 2 π ⇒ tan 2 θ tan 3 α = 1 ⇒ 1 − x 2 2 x × 1 − 3 ( 3 x ) 2 3 ( 3 x ) − ( 3 x ) 3 = 1 ⇒ 8 1 x 4 − 4 6 x 2 + 1 = 0 ⇒ x 2 = 2 × 8 1 4 6 ± 4 6 2 − 4 × 8 1 × 1 = 8 1 2 3 ± 8 7 = d a − b c A s a l l a r e + v e a = 2 3 , b = 8 , c = 7 , d = 8 1 ⇒ a + b + c + d = 1 1 9
Same method :)
Problem Loading...
Note Loading...
Set Loading...
Our main solution here is to use the trigonometric identity (this is yours to prove since this is trivial by using the tan addition identity):
arctan (a) + arctan (b) = arctan([a+b]/[1 - ab]).
We can separate the terms in order to use the identity given above, where
4 arctan (x) + 4 arctan (3x) + 2 arctan (3x) = pi
4 (arctan [4x / (1 - 3x^2)]) + 2 arctan (3x) = pi
Separating further the terms:
2 (arctan [4x / (1 - 3x^2)]) + 2 (arctan [4x / (1 - 3x^2)]) + 2 arctan (3x) = pi
2 (arctan [4x / (1 - 3x^2)]) + 2 arctan ([7x - 9x^3]/[1 - 15x^2]) = pi
2 arctan ([27x^5 - 90x^3 + 11x] / [81x^4 - 46x^2 + 1]) = pi
Note: The operations here are all simplified. It is your work to use these identities and simplify after adding and dividing.
arctan ([27x^5 - 90x^3 + 11x] / [81x^4 - 46x^2 + 1]) = pi/2
[27x^5 - 90x^3 + 11x] / [81x^4 - 46x^2 + 1] = tan(pi/2) = undefined
There exists such x^2 that will make the equation undefined and this is when 81x^4 - 46x^2 + 1 = 0 where for all x's is a vertical asymptote and noticing that the common factor between the numerator and denominator is only 1. Hence, we solve the quadratic equation above for x^2.
We call the quadratic formula to solve for x^2.
x^2 = [23 +- 8sqrt(7)]/81 after simplification.
Hence, 119 is the answer.